2020
DOI: 10.1136/annrheumdis-2020-218048
|View full text |Cite
|
Sign up to set email alerts
|

Lung involvement in macrophage activation syndrome and severe COVID-19: results from a cross-sectional study to assess clinical, laboratory and artificial intelligence–radiological differences

Abstract: ObjectivesTo evaluate the clinical pictures, laboratory tests and imaging of patients with lung involvement, either from severe COVID-19 or macrophage activation syndrome (MAS), in order to assess how similar these two diseases are.MethodsThe present work has been designed as a cross-sectional single-centre study to compare characteristics of patients with lung involvement either from MAS or severe COVID-19. Chest CT scans were assessed by using an artificial intelligence (AI)-based software.ResultsTen patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…In the view of the limitations for applying the standard HLH criteria, most studies have used the HScore, a classification score developed specifically for secondary, and especially malignancy associated, HLH in adults, that does not include any cytokine-related criteria [ 3 ]; a HScore > 169 has a sensitivity of 93% and a specificity of 86% for a HLH diagnosis. In studies searching for HLH in severe COVID-19 patients, there were 17 (4%) out of 428 patients that had a score > 169 [ 33 , 34 , 37 , 41 , 42 ] (Table 2 ) , while in the individual reported cases summarised in Table 3 , 7 (12%) had a score equal or higher than 169. The use of HScore for COVID-19 patients has been questioned after highlighting some limitations regarding temperature, leukopenia (the score does not distinguish between neutropenia and lymphocytopenia), and the lack of published data on hypertriglyceridaemia, splenomegaly, hepatomegaly and BM haemophagocytosis, and therefore, some authors recommend against their use due to a potential lack of sensitivity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the view of the limitations for applying the standard HLH criteria, most studies have used the HScore, a classification score developed specifically for secondary, and especially malignancy associated, HLH in adults, that does not include any cytokine-related criteria [ 3 ]; a HScore > 169 has a sensitivity of 93% and a specificity of 86% for a HLH diagnosis. In studies searching for HLH in severe COVID-19 patients, there were 17 (4%) out of 428 patients that had a score > 169 [ 33 , 34 , 37 , 41 , 42 ] (Table 2 ) , while in the individual reported cases summarised in Table 3 , 7 (12%) had a score equal or higher than 169. The use of HScore for COVID-19 patients has been questioned after highlighting some limitations regarding temperature, leukopenia (the score does not distinguish between neutropenia and lymphocytopenia), and the lack of published data on hypertriglyceridaemia, splenomegaly, hepatomegaly and BM haemophagocytosis, and therefore, some authors recommend against their use due to a potential lack of sensitivity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among biochemical parameters, the typical triad of abnormalities in HLH includes hypertriglyceridaemia, hypofibrinogenaemia and hyperferritinaemia. Triglyceride levels are not usually measured in the standard of care of patients with COVID-19, and in studies focused on investigating HLH-related features in COVID-19, 90/975 (9%) patients showed hypertriglyceridaemia (Table 2 ) [ 33 35 , 37 , 38 ], and one study has reported no significant differences for mean TG levels between non-severe and severe COVID-19 patients [ 44 ]. In addition, the use of tocilizumab should always be discarded as a potential cause of hypertriglyceridaemia in patients with COVID-19 [ 45 , 46 ].…”
Section: Haemophagocytic Syndrome Related To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The cardinal target organ of COVID-19 is the lung, causing an acute respiratory distress syndrome. Recently, Ruscitti et al conducted a study to compare the difference of clinical manifestation, laboratory tests, and radiological imaging in patients with lung involvement between severe COVID-19 and MAS secondary to AOSD (71). More patients in the COVID-19 group presented with ground-glass opacities (GGOs) compared with those in the group of MAS secondary to AOSD.…”
Section: Discussionmentioning
confidence: 99%
“…Severe COVID-19 may be considered part of the (heavy:light:heavy) HLH chain spectrum due to overlapping clinical features 75 , 76 . However, both laboratory and radiological differences between secondary HLH and severe COVID-19, which did not appear as part of the HLH spectrum, exist [77] . For better understanding, readers are invited to read the articles references here.…”
Section: Pathophysiology Of Hyperferritinemia In Covid-19 Patientsmentioning
confidence: 95%